Le gisement de Crévéchamps (Lorraine) Du Néolitique à l'époque romaine dans la vallée de la Moselle - Koenig, Marie-Pierre (Documents d'archéologie française, 2016)
Archaeological prospection by test trenches covering about fort Y hectares of a future gravel pit and archaeological excavations of about 15 hectares, conducted between 1989 and 1994, allowed a study of human occupation, settlement history and landscape change from the Neolithic to the Roman times. The study area covers an exceptionally large surface situated in the Holocene river plain of the Moselle valley near Crévéchamps, Meurthe-et-Moselle. With about 7000 recorded archaeological features, Marie-Pierre Koenig and her team followed a rigorous methodology to determine how, overt wo millennia, humans settled and lived in a landscape and settlement micro-region impacted by the shifting course of the Moselle river. The scientific approach comprises the grouping of the archaeological features according to their function, a typological analysis of them and the study of their setting in the former landscape, reconstructed by means of different environmental analyses. Due to a remarkable study of the Bronze and Iron pottery, supported by comparisons with numerous sites of Northwestern Europe, the authors suggest an evolutionary scheme of the settlement and its history. This approach is already considered to be a major reference for settlement archaeology. The first land clearing began during Neolithic times. During the following Bronze and Iron Age, settlement density increased. Palisades, roads and trenches followed the natural delimitations formed by the ancient river channels, while agricultural activities on the gravel domes in the alluvial river plain were moved cyclically. Later, the Gallo-Roman population drained and parcelized the land. Farms continued to exist, with Gallic traditions persisted, but human activities became more diverse with the opening of a large clay-pit -until a flood in the 2nd century AD led the occupants to abandon this excessively humid zone. The scientific results are enriched by a meticulous iconography and ample documentation: pottery catalogue, building descriptions, results of 14C datings, an index of the features, general maps and an index locorum. Chapter summaries given in English and German provide international readers with quick access to the main results.